An efficient approach toward the synthesis of the A/B rings of ouabain - Plano, Maria Fernanda (2006)
The synthesis of the highly functionalized A/B ring related to ouabain has been accomplished efficiently from commercially available α-tetralone. A key Birch reductive alkylation allows the building of an angularly substituted decalone that was adequately functionalized to produce the intermediate 2c.